A new species of Woronina from decomposing plant litter in ponds of Varanasi - R. DAYAL, USHA KIRAN and (Indian Phytopathology, 2012)
Woronina includes four known species so far; none have been reported from Chara. The thallus structure IS much different from any reported species. W. charii is being described as a new species from India.